Developing a training strategy for teenage athletes in mixed martial arts for high-level competitions - Shtefiuk, I.; Tsos, A.; Chernozub, A.; Aloshyna, A.; Marionda, I.; Syvokhop, E.; Potop, V. (Journal of Physical Education and Sport, 2024)
Background With the increasing demands aced by teenage athletes in mixed martial arts (MMA) competitions, there is a pressing need for scientists to develop innovative training. This study aims to formulate a strategy for training teenage athletes to excel in high-level MMA competitions, leveraging the physiological characteristics of neuromuscular system adaptation to stress-inducing stimuli. Additionally, the practical efficacy of this strategy is be assessed.